Baicalin triggers apoptosis, inhibits migration, and enhances anti‐tumor immunity in colorectal cancer via TLR4/NF‐κB signaling pathway. Issue 3 (20th March 2021) - Song, Linjiang; Zhu, Shaomi; Liu, Chi; Zhang, Qinxiu; Liang, Xin
Abstract: Aberrant activation of the nuclear factor‐kappa B (NF‐κB) signaling pathway is closely implicated in colorectal cancer (CRC) growth, metastasis, and immune escape. In the present study, we reported natural derived compound of baicalin (BA), an efficient inhibitor of NF‐κB, with good anti‐tumor effect on CRC. CCK8 and colony formation assays showed that Baicalin significantly inhibit viability and proliferation in HCT‐116 and CT26 cells. Additionally, Baicalin dramatically triggers mitochondria‐mediated apoptosis in both HCT‐116 and CT‐26 cells, which is evidenced by loss of mitochondrial membrane potential and elevated cellular reactive oxygen species level. Treatment with Baicalin suppresses migration and invasion of CT26 cells by impairing TLR4/NF‐κB signaling pathway. What's more, administration of Baicalin significantly retarded tumor growth rate in a subcutaneous xenograft tumor mouse model of CT26 cells. Treatment with Baicalin could ameliorate tumor immunosuppressive environment by downregulation of PD‐L1 expression and proportion of myeloid‐derived suppressor cells (MDSCs) and upregulation of percent of CD4 + and CD8 + T cells in CT26 tumors, thus improving anti‐tumor immunity. In conclusion, our study demonstrated that baicalin triggers apoptosis, inhibits migration, and enhances anti‐tumor immunity in colorectal cancer via TLR4/NF‐κB signaling pathway, suggesting it might serve as a potential candidate drug for the treatment of CRC. Practical applications: In the present study, we reported natural derived compound of baicalin (BA), an efficient inhibitor of NF‐κB, with good anti‐tumor effect on CRC. We demonstrated that baicalin triggers mitochondria‐mediated apoptosis, inhibits migration, and improves anti‐tumor immunity in colorectal cancer via TLR4/NF‐κB signaling pathway. Abstract : Baicalin dramatically triggers mitochondria‐mediated apoptosis in colorectal cancer cells. Migrative and invasive abilities of colorectal cancer cells were inhibited by treatment with baicalin. Baicalin enhances anti‐tumor immunity in colorectal cancer via TLR4/NF‐κB signaling pathway.